Филогенетический анализ геномов популяций свиней европейского и азиатского происхождения - Хохлов, А.М.; Барановский, Д.И. (Фактори експериментальної еволюції організмів, 2016)
Aim. In evolution process – gradual changes in heritable structures of species – changes not only of the number of genes, but and their properties, frequency and direction of variation. Changes of gene frequency that are going-on for the small time period are attributed to microevolution. Breed forming processes in swine-breeding are miroevolutional processes that are take place from ancestral forms Sus scrofa scrofa to current special swine breeds. Methods. For a study and transformation used the method of imunogenetics analysis of antigens of red corpuscles, based on determination of molecular-genetic markers of representatives of modern breeds, initial breeds and distant paternal forms. Results. In this work are submitted results of investigations of genetic blood group systems in populations Sus scrofa ferns and Sus scrofa asian, aboriginal local breeds (mangalic, kahetin, Vietnam), base breeds (big white, berkshir) and current special breeds (landrace, duroc, pietrain, etc.). By frequency dynamic of european and asian animal origin alleles, are rewieved genesis and microevolution of big white and other highly productive breeds by forming global gene pool of current swinebreeding different countries. Conclusions. On the basis of plant-breeding-genetic analysis of population of domestic and wild pigs the paradigm of genetics-popoulation processes what be going on at domesticating of pigs is formed. It is set the method of imuno-genetics analysis, domestication alleles that pigs have Fa, Gb, Af, Hb, Amc, TfA, CpB et al. Genetic likeness on separate markers (F, Tf, Cp of and other) in the population of the wild European wild boar specifies on community of their origin, and further the late display of polymorphism on separate locus for the Asian wild boar confirms hypothesis suggested a by us about later his origins. Keywords: population, breed, polymorphism, domestication, phylogenesis, frequency of alleles.